STRATEGI KESOPANAN BERBAHASA JEPANG DALAM KORESPONDENSI SURAT ELEKTRONIK BISNIS YANG DISARANKAN OLEH PENUTUR ASLI BAHASA JEPANG - Rike Febriyanti (Erudio Journal of Educational Innovation, 2018)
From 2016 to 2017, the writer composed a pocket book correspondence business email in Japanese language for her students who were completing internship program at Japanese companies in Indonesia. To assess the quality of the book in the perspective of native Japanese speakers who were business practitioners in Indonesia, the writer asked the native speakers to assess and to give advice on the quality of the book. The native speakers then suggested some aspects to be reviewed in the pocket book to make the sentences more polite without losing their practicality and effectiveness. This current study attempted to investigate the use of politeness strategies as suggested by two Japanese native speakers, in the theoretical framework as defined by Brown and Levinson (1978), among businessmen in their written international business communication especially in email. Based on interview and analysis made by the native speakers, the writer found that they suggested using positive and shorter expressions in expressing orders, requests, offers, complaints, apologies, and suggestions.